Assessing the Effectiveness of Disaster-Resilient Villages in Flood Mitigation: A Case Study of Tanete Riaja District - Rezky Nur Padhilah; Muliana (P3M Stia Al Gazali Barru and Meraja media, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal